Pandangan Islam Terhadap Keadilan Gender: Analisis Tafsir Maudhu'i - Puspita Amanah; Sa'idah, Rija Fhaziyah; Yakub, Riki (Shād : Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
Regarding the issue of gender that is currently circulating, there are still many patriarchal people who consider women to be weak and not worthy of having a higher education. The aim of the research is to explain the concept and emphasize gender justice in relation to several outstanding issues. This research method uses descriptive research by collecting pre-existing data taken from previous research on gender. The results of this research show that gender justice has been explained in due course. Al-Hujurat: 13 which can be concluded that men and women have their own rights, there is no explanation about men being stronger than women or women being stronger than men, while Allah's judgment on humans is not physical, mental, or position but from a person's faith. Keywords:Gender, Issues, Interpretation, Maudhu'i